Hukum Acara Perdata dalam Penyelesaian Sengketa Perdata: Tinjauan Teori Hukum Responsif Nonet dan Selznick - I Putu Windu Semara Putra; I Gede Agus Kurniawan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Civil procedural law is the primary instrument for resolving civil disputes in court. However, in practice, criticism often arises that existing procedures tend to be rigid, formalistic, and do not always meet the needs of justice seekers. The responsive legal theory developed by Nonet and Selznick offers an analytical framework for assessing the extent to which the legal system is able to adapt to the aspirations and interests of society. This study aims to examine how civil procedural law in Indonesia functions in resolving civil disputes and to assess the extent to which its application can be categorized as responsive law, according to Nonet and Selznick's theory. This study uses a normative-juridical approach with a literature review. Data were obtained from relevant laws and regulations, legal literature, and court decisions, then analyzed qualitatively through the perspective of responsive legal theory. The analysis shows that although civil procedural law has provided a formal mechanism for resolving disputes, its implementation is often procedural and slow. This creates a gap between legal norms and the reality of justice seekers. Within the theoretical framework of Nonet and Selznick, Indonesian civil procedural law tends to be at the stage of "autonomous law," which emphasizes formal rules, but has not yet fully reached the stage of "responsive law," which is oriented towards substantive justice and social needs. Civil procedural law needs to be directed in a more responsive direction by simplifying procedures, improving access to justice, and emphasizing fair resolution for the parties. Thus, law becomes not only a procedural tool, but also an instrument of justice that lives within society.